Association rules recommendation algorithm supporting recommendation nonempty - Ming HE; Wei-shi LIU; Jiang ZHANG (Tongxin xuebao)
Existing association rule recommendation technologies were focus on extraction efficiency of association rule in data mining.However,it lacked consideration of recommendation balance between popular and unusual data and efficient processing.In order to improve the quality and efficiency of personalized recommendation and balance the recommendation weight of cold and hot data,the problem of mining frequent itemset based on association rule was revaluated and analyzed,a new evaluation metric called recommendation RecNon and a notion of k-pre association rule were defined,and the pruning strategy based on k-pre frequent itemset was designed.Moreover,an association rule mining algorithm based on the idea was proposed,which optimized the Apriori algorithm and was suitable for different evaluation criteria,reduced the time complexity of mining frequent itemset.The theoretic analysis and experiment results on the algorithm show that the method improved the efficiency of data mining and has higher RecNon,F-measure and precision of recommendation,and efficiently balance the recommendation weight of cold data and popular one.